Japan: The Earliest Evidence of Complex Technology for Creating Durable Coloured Goods - Matsumoto Naoko (Open Archaeology, 2018)
The invention of lacquer technology is significant in history as the first evidence of the use of an organic substance in creating durable coloured objects. By focusing on the evidence from the Jomon Period, Japan, this article clarifies the nature of complex technology and knowledge required for lacquer production, presents how lacquer technology enhanced our creative ability, and discusses its significance in human history. Lacquer technology was invented in the course of increasing human-plant interaction in the warming climate of the early Holocene. Personal ornaments coated with red lacquer are the most conspicuous throughout the Jomon Period from the beginning of lacquer technology. Strong attention to colour and intensive application on personal ornaments indicate that the creation of symbolic artefacts in social context was at the core of Jomon lacquer technology.